Política, sociedade, crime e loucura : inimputabilidade feminina no discurso médico jurídico do manicômio judiciário do Rio Grande do Sul (1925-1939) - Carvalho , Jóice Anne Alves (2019)
The history of Brazilian society is marked by patriarchalism and strong delimitation of the social roles of women and men. During the first half of the twentieth century the Brazilian political scenario was marked by several projects for the construction of the Nation. In this context, the eugenic and hygienic discourses converged to the characterization of the ideal individual that should compose this social organism. Thus, the representation of women, through these speeches, was based and legitimized by femininity, belonging to the private space of the home, having as its main objective the motherhood and the education of their children. In this sense, in addition to the physical standard rigorously instituted by the eugenic bias, it was also sought to establish the moral standards to be followed in the legal constitution of the individual. Therefore, the object of analysis of this work is the female inimputability from the sources found in the Judiciary Asylum of Rio Grande do Sul, from 1925-1939. It is understood that in the time frame analyzed the practices in total institutions demonstrated the cohesion between the eugenic medical discourse and the reformulation of the brazilian legal discourse. From publications by eugenic practitioners, the 1890 Penal Code, the 1916 Penal Code, and the inmates' papers at the institution, an analysis of female madness and crime was developed. In the analyzed period, women represented approximately 10% of the inmates in the Judicial Asylum, which led us to develop this analysis was its quantitative character, but the importance of the concepts present in medical reports to infer the inimputability to these women. Therefore, it was evidenced not only the construction of the character of female inimputability from the displacements of the concept of madness, but also, the normalization by which women suffered in the period.